2011
DOI: 10.1155/2011/270594
|View full text |Cite
|
Sign up to set email alerts
|

Self-Care Recommendations of Middle-Aged and Older Adults with Sickle Cell Disease

Abstract: Self-care management is an important part of living with a chronic illness. Sickle cell disease (SCD) is a chronic disease with acute, painful exacerbations that often results in a shortened life expectancy. Some middle-aged and older adults with SCD lived with the disease prior to having a diagnosis and without modern advances. The purpose of this study is to share the self-care recommendations of middle-aged and older adults with SCD. Using descriptive qualitative methods, data were gathered through semistru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
61
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(67 citation statements)
references
References 16 publications
6
61
0
Order By: Relevance
“…Use of self-care in long-term disease management is positively influenced by support from family, friends, and health care professionals (Schulman-Green et al, 2012). Individuals who receive higher levels of social support are more likely to feel as though they have the ability to perform self-care and actually do so to maintain health (Jenerette, Brewer, & Leak, 2011). In this study, higher SCD self-efficacy was associated with better self-care, supporting earlier research that found that self-efficacy has been associated with better self-care in chronic disease (Frei et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of self-care in long-term disease management is positively influenced by support from family, friends, and health care professionals (Schulman-Green et al, 2012). Individuals who receive higher levels of social support are more likely to feel as though they have the ability to perform self-care and actually do so to maintain health (Jenerette, Brewer, & Leak, 2011). In this study, higher SCD self-efficacy was associated with better self-care, supporting earlier research that found that self-efficacy has been associated with better self-care in chronic disease (Frei et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In a study assessing strategies used by adults with SCD to manage their disease, themes included self-awareness, emotional support, career selection and success factors, nutrition, advocacy, knowledge, physical activity, and complementary and alternative medicine (Tanabe et al, 2010). In middle-aged and older adults, identified self-care recommendations were physiologic (warmth, hydration, rest, good food, and avoiding drinking, smoking, and using drugs), psychological (knowledge and understanding of the disease, listening to and learning about the body, prayer, and social support), and provider-related (knowledgeable health care providers and following providers’ orders) (Jenerette, Brewer & Leak, 2011). Self-care has many benefits and is correlated with a number of variables, but it is unclear which variable is most influential, particularly in the young adult population.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recognizing the cues to an evolving SCD-related acute pain episode (usually referred to as a painful crisis) and responding appropriately may be an important part of knowing the body and self-care management, especially for young adults living with this disease. Some young adults with SCD may be overly dependent on emergency departments for care as they transition from pediatric to adult providers (Hemker, Brousseau, Yan, Hoffman, & Panepinto, 2011); they have not yet acquired the self-care pain management skills that older adults have described as “learning their bodies,” and thus, are at particularly high risk for poor pain outcomes (Jenerette & Lauderdale, 2008;Jenerette, Leak, & Sandelowski, 2011). A significant part of learning the body is recognizing the cues to an evolving sickle cell crisis and responding appropriately.…”
mentioning
confidence: 99%
“…Management of SCD occurs primarily at home and depends on self-care. Self-care strategies include the aforementioned pharmacologic methods, as well as nonpharmacologic methods (e.g., warmth, hydration, rest, good food, avoiding alcohol and drugs, listening to and learning about the body, prayer, social support) (Jenerette, Brewer, & Leak, 2011). …”
Section: Managementmentioning
confidence: 99%